SALL4 oncogene is an immunogenic antigen presented in various HLA-DR contexts. (3rd April 2018) - Kroemer, Marie; Spehner, Laurie; Mercier-Letondal, Patricia; Boullerot, Laura; Kim, Stefano; Jary, Marine; Galaine, Jeanne; Picard, Emilie; Ferrand, Christophe; Nguyen, Thierry; Larosa, Fabrice; Adotévi, Olivier; et al.
ABSTRACT: Purpose : To investigate the immunoprevalence of SALL4-derived peptides in healthy volunteers and cancer patients.Experimental Design : A multistep approach including prediction algorithms was used to design in silico SALL4-derived peptides theoretically able to bind on common HLA-DR and HLA-A/B molecules. The presence of T-cell responses after a long term T-cell assay (28 days) against SALL4 was monitored in 14 healthy donors and the presence of T-cell responses after a short term T-cell assay (10 days) was monitored in 67 cancer patients using IFN-γ ELISPOT assay. A T-cell clone specific for the immunoprevalent A18 K-derived peptide was isolated, characterized and used as a tool to characterize the natural processing of A18 K.Results : A SALL4 specific T-cell repertoire was present in healthy donors (8/14) and cancer patients (29/67) after short term T-cell assay. We further identified two immunoprevalant SALL4-derived peptides, R18 A and A18 K, which bind MHC-class II. In parallel, an A18 K specific Th1 clone recognized monocyte derived Dendritic Cell (moDC) loaded with SALL4 containing cell lysate. The level of IFN-γ secreted by specific T-cell clone was greater in presence of moDC loaded with SALL4 containing cell lysate (49.23 ± 14.02%) than with moDC alone (18.03 ± 3.072%) (p = 0.0477)Conclusion : These results show for the first time immunogenicity of SALL4 oncogenic protein-derived peptides, especially A18 K and R18 A peptides and make them potential targets for personalized medicine. Thus, SALL4 possess major characteristics of a tumor antigen.